Direct Medical Cost of Influenza-Related Hospitalizations among Severe Acute Respiratory Infections Cases in Three Provinces in China - Zhou, Lei; Situ, Sujian; Huang, Ting; Hu, Shixiong; Wang, Xianjun; Zhu, Xiaoping; Gao, Lidong; Li, Zhong; Feng, Ao; Jin, Hui; Wang, Shiyuan; Su, Qiru; et al. (PLOS ONE, 2013)
Background Influenza-related hospitalizations impose a considerable economic and social burden. This study aimed to better understand the economic burden of influenza-related hospitalizations among patients in China in different age and risk categories. Methods Laboratory-confirmed influenza-related hospitalizations between December 2009 and June 2011 from three hospitals participating in the Chinese Severe Acute Respiratory Infections (SARI) sentinel surveillance system were included in this study. Hospital billing data were collected from each hospital’s Hospital Information System (HIS) and divided into five cost categories. Demographic and clinical information was collected from medical records. Mean (range) and median (interquartile range [IQR]) costs were calculated and compared among children (≤15 years), adults (16–64 years) and elderly (≥65 years) groups. Factors influencing cost were analyzed. Results A total of 106 laboratory-confirmed influenza-related hospitalizations were identified, 60% of which were children. The mean (range) direct medical cost was $1,797 ($80–$27,545) for all hospitalizations, and the median (IQR) direct medical cost was $231 ($164), $854 ($890), and $2,263 ($7,803) for children, adults, and elderly, respectively. Therapeutics and diagnostics were the two largest components of direct medical cost, comprising 57% and 23%, respectively. Cost of physician services was the lowest at less than 1%. Conclusion Direct medical cost of influenza-related hospitalizations imposes a heavy burden on patients and their families in China. Further study is needed to provide more comprehensive evidence on the economic burden of influenza. Our study highlights the need to increase vaccination rate and develop targeted national preventive strategies.